Cerebral vasospasm: current understanding. Issue 5 (October 2016) - Rao, Ganne S. Umamaheswara; Muthuchellappan, Radhakrishnan
Abstract : Purpose of review: With recent research trying to explore the pathophysiologic mechanisms behind vasospasm, newer pharmacological and nonpharmacological treatments are being targeted at various pathways involved. This review is aimed at understanding the mechanisms and current and future therapies available to treat vasospasm. Recent findings: Computed tomography perfusion is a useful alternative tool to digital subtraction angiography to diagnose vasospasm. Various biomarkers have been tried to predict the onset of vasospasm but none seems to be helpful. Transcranial Doppler still remains a useful tool at the bedside to screen and follow up patients with vasospasm. Hypertension rather than hypervolemia and hemodilution in 'Triple-H' therapy has been found to be helpful in reversing the vasospasm. Hyperdynamic therapy in addition to hypertension has shown promising effects. Endovascular approaches with balloon angioplasty and intra-arterial nimodipine, nicardipine, and milrinone have shown consistent benefits. Endothelin receptor antagonists though relieved vasospasm, did not show any benefit on functional outcome. Summary: Endovascular therapy has shown consistent benefit in relieving vasospasm. An aggressive combination therapy through various routes seems to be the most useful approach to reduce the complications of vasospasm.